Experimental Investigation of Spray Drying Breakup Regimes of a PVP-VA 64 Solution Using High-Speed Imaging - Cooper Welch; Mobaris Khawar; Benjamin Böhm; Andreas Gryczke; Florian Ries (Pharmaceutics)
Background: Atomization plays a key role in spray drying, a process widely used in the pharmaceutical, chemical, biological, and food and beverage industries. In the pharmaceutical industry, spray drying is particularly important in the preparation of amorphous solid dispersions, which enhance the bioavailability of active pharmaceutical ingredients when mixed with a polymer. Methods: In this study, a 3D-printed adaptation of a commercial spray dryer nozzle (PHARMA-SD® PSD-1, GEA Group AG) was used to investigate the atomization of PVP-VA 64 polymer solutions under varying flow conditions using high-speed diffuse back-illumination. Results: Unlike pure water, the atomization process of the polymer solution was governed by viscous effects rather than surface tension, as indicated by stringing effects in the liquid core and the formation of larger droplets. In addition, the classical Ohnesorge diagram accurately predicted the atomization regime with increasing Reynolds numbers and could be modified to reasonably predict the breakup regime by considering the transitions between regime boundaries. Conclusions: The use of such a modified diagram facilitates the efficient selection of viscous fluid solutions and process parameters to achieve complete spray formation.